Experimental and Computational Studies of Incorporation of Cyano Transition Metal Complexes in Potassium Chloride Crystals - Carter, Damien; Ogden, Mark; Rohl, Andrew (CSIRO PUBLISHING, 2003)
Experimental and computational studies of the incorporation of hexacyanoferrate(II), hexacyanocobaltate(III), and hexacyanoferrate(III) into potassium chloride crystals are described. The experimental results showed that the extent of incorporation follows the trend, hexacyanoferrate(II) >> hexacyanoferrate(III) > hexacyanocobaltate(III). Computational modelling produced replacement energies that match the experimental trend. The calculated geometry of the incorporated complexes was also found to match well with previous experimental results.